Experimental Background Preceding Direct Laser-Assisted Angioplasty in the Human Coronary Anatomy - Nordstrom, Leonard A. (1989)
The central question that faces coronary laser investigators is whether interaction between laser energy and target tissues can be controlled in a dynamic in vivo environment. In considering this question, the author reviews the in vitro and in vivo experiments that his center carried out before it began using laser angioplasty for clinical coronary applications. The in vitro experiments were undertaken to enable coaxial delivery of argon laser energy; to monitor the fluorescence of the lens assembly; to determine the effect of a saline infusion on the conduction of thermal energy; to evaluate the potential risk posed by embolization of debris; and to analyze the effects of increased beam divergence. The in vivo experiments were undertaken to examine the results of coaxial alignment of the laser beam in a rabbit model and to test the complete delivery system in dogs. The author also discusses his institution's 1st clinical trials of laser angioplasty in peripheral arteries, and its initial use of the laser technique in human coronary vessels. (Texas Heart Institute Journal 1989;16:158-62)